Genetic Deletion of Emp2 Does Not Cause Proteinuric Kidney Disease in Mice - Donnan, Michael D.; Scott, Rizaldy P.; Onay, Tuncer; Tarjus, Antoine; Onay, Ummiye Venus; Quaggin, Susan E. (Frontiers in Medicine, 2019)
Nephrotic syndrome is one of the most common glomerular diseases in children and can be classified on the basis of steroid responsiveness. While multiple genetic causes have been discovered for steroid resistant nephrotic syndrome, the genetics of steroid sensitive nephrotic syndrome remains elusive. Mutations in Epithelial Membrane Protein 2 (EMP2), a member of the GAS3/PMP22 tetraspan family of proteins, were recently implicated as putative monogenic cause of steroid sensitive nephrotic syndrome. We investigated this hypothesis by developing Emp2 reporter and knockout mouse models. In lacZ reporter mice (engineered to drive expression of the enzyme -galactosidase under the control of the endogenous murine Emp2 promoter), Emp2 promoter activity was not observed in podocytes but was particularly prominent in medium- and large-caliber arterial vessels in the kidney and other tissues where it localizes specifically in vascular smooth muscle cells but not in the endothelium. Strong Emp2 expression was also found in non-vascular smooth muscle cells found in other organs like the stomach, bladder, and uterus. Global and podocyte-specific Emp2 knockout mice were viable and did not develop nephrotic syndrome showing no evidence of abnormal glomerular histology or ultrastructure. Altogether, our results do not support that loss of function of EMP2 represent a monogenic cause of proteinuric kidney disease. However, the expression pattern of Emp2 indicates that it may be relevant in smooth muscle function in various organs and tissues including the vasculature.